Letters of Peter Torchakov from the Second Half of the 17th Century: Themes and Graphic Features - Ryko, Anastasiia (Slavistica Vilnensis, 2025)
The article focuses on the analysis of the private letters of Peter Torchakov, the son of a mid-17th-century merchant from Ivangorod. The set of Peter Torchakov’s letters is part of the unpublished archive of Parthenius Torchakov, stored in the National Archives of Estonia, and consists of 16 letters written between 1661 and 1667. Special attention is paid to two aspects: the thematic content of the letters and their graphic features. The letters not only intertwine business and personal matters, which is typical of correspondence during that period, but also partially reflect political events. In addition, these “gramotki” demonstrate graphic diversity. The analysis of the graphic variations of certain letters and the use of graphically paired letters makes it possible to divide the entire corpus of letters into two parts and associate these graphic systems with the thematic content of the letters. The presence of different graphic subsystems in texts written by the same author suggests that the choice of writing style was a conscious decision reflecting the content of the text. This conclusion finds parallels in book writings, where the dependence of handwriting on the function of the text was also observed.